The Effectiveness of Comic Strip As Media to Improve the Students’ Reading Comprehension on Narrative Text of MTs Ar-Rahman Langkat - Sari Manik, Rudang Mayang (KnE Social Sciences, 2019)
In this research, the writer would deal with reading skill based on the consideration that success in reading will be very important for students both for academic and vocational advancement. For mor than a quarter of a century language teachers have been dominated by the idea that speech is the primary from of languange, writing is secondary. So, it is logic that there is such a common sense that teaching languange is nothing more than a remedial stage of preparation to the more rigorous. Moreover, reding is regarded as somewhat dull because today’s generationg ets philosopy from thr movie. In fact, studying literature can assure intellectual stimulation even at the beginning stages of learning. According to the statement above, there is a challenge on the foreign language teacher to provide exposure to language and to provide opportunities for learning through classroom activities. In class, teacher have significant rule to bring out the fun class to the students. So, teacher should try to get students read and develop their skills that are aimed to improve their ability and will to read. Theey should be a good facilitator in creating nd building an effecctive reading class. One way to conduct the clss to be more interesting is by using a fresh and interesting material to be brought to clas. This case is also happend in MTs Ar-Rahman Langkat that only some of material in the book about reading comprehension and many students can not understand what the next talk about. In other words, comic is unification , work of art among fine literary works in which there are usual froms are the verbal explanation in fixedd sequence and has cartoon story as theme. Reading cimics is more than the material in hand, that it involves a certain immersion into the cultural of the comics that one readers to get the right visualization. Teacher should be sekective in choosing teaching media/ aids. In the writer’s opinion, teaching English on reading skill using comic strips was one of teacjing aid which student’s were given chance to learn English more fun. Keywords: effectiveness, comic, reading comprehension.